2006
DOI: 10.1055/s-2005-873072
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Mesenchymal Hamartoma Associated with 19q Translocation. A Call for More Radical Surgical Resection

Abstract: Hepatic mesenchymal hamartoma is a rare benign tumour in children. It is often large and centrally located in the liver at diagnosis, making surgical resection difficult; thus non-radical resection has been proposed in the past as acceptable management. However, a literature survey and a case with recurrence associated with cytogenetic anomalies suggest that radical liver surgery (resection with a margin of normal liver parenchyma, as for malignant tumour) should be recommended for mesenchymal hamartoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Translocations or more complex rearrangements involving19q13.3–19q13.4 are a feature of the karyotype of virtually every case of MHL that has been subjected to conventional cytogentical analysis (Speleman et al, 1989; Ishak et al, 2001; Murthi et al, 2003; Rakheja et al, 2004; Sharif et al, 2006; Siddiqui and McKenna, 2006; Talmon and Cohen, 2006), and are also a recurring feature of UES arising in MHL (Sawyer et al, 1996; Lauwers et al, 1997; O'Sullivan et al, 2001). Similarly, translocations or other rearrangements involving 11q11–13 are present in most MHL (Speleman et al, 1989; Ishak et al, 2001; Murthi et al, 2003; Rakheja et al, 2004; Sharif et al, 2006; Siddiqui and McKenna, 2006) and a subset of UES arising in MHL (O'Sullivan et al, 2001). Thus, it is likely that the t(11;19) translocation is related to the development of MHL but that additional alterations of other loci are required for the tumorigenesis of UES, consistent with recent comparative genomic hybridization results that show UES is characterized by multiple amplifications and deletions (Sowery et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translocations or more complex rearrangements involving19q13.3–19q13.4 are a feature of the karyotype of virtually every case of MHL that has been subjected to conventional cytogentical analysis (Speleman et al, 1989; Ishak et al, 2001; Murthi et al, 2003; Rakheja et al, 2004; Sharif et al, 2006; Siddiqui and McKenna, 2006; Talmon and Cohen, 2006), and are also a recurring feature of UES arising in MHL (Sawyer et al, 1996; Lauwers et al, 1997; O'Sullivan et al, 2001). Similarly, translocations or other rearrangements involving 11q11–13 are present in most MHL (Speleman et al, 1989; Ishak et al, 2001; Murthi et al, 2003; Rakheja et al, 2004; Sharif et al, 2006; Siddiqui and McKenna, 2006) and a subset of UES arising in MHL (O'Sullivan et al, 2001). Thus, it is likely that the t(11;19) translocation is related to the development of MHL but that additional alterations of other loci are required for the tumorigenesis of UES, consistent with recent comparative genomic hybridization results that show UES is characterized by multiple amplifications and deletions (Sowery et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In all reported cases with cytogenetic analysis, an aberration involving chromosomal region 19q13.4 has been present. Specifically, the t(11;19)(q13;q13.4) has been reported in three cases (Mascarello and Krous, 1992; Bove et al, 1998; Rakheja et al, 2004), whereas t(11;19)(q13;q13.3), t(15;19)(q15;q13.4), a complex rearrangement involving 11q2, 17p11 and 19q13.3, and an interstitial deletion del(19)(q13.1q13.4) have each been reported in single cases (Speleman et al, 1989; Murthi et al, 2003; Sharif et al, 2006; Talmon and Cohen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the observed translocation did not lead to any fusion genes. (11)t (11;19)(q13;q13), der (19)t (11;19) The chromosomal translocation t(11;19)(q13;q13) has also been reported as an acquired, recurrent genomic rearrangement in mesenchymal hamartoma of the liver, which is a rare benign tumor in children (23)(24)(25)(26)(27)(28). Molecular studies of such tumors showed that the t(11;19)(q13;q13) of mesenchymal hamartoma was associated with deregulation of gene expression (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic studies have described a balanced translocation involving the same breakpoint on chromosome 19 (band 19q13.3 or 4) in seven MHL tumors [8][9][10][11][12][13][14] (Table 1). Five had the balanced translocation t(11;19)(q13;q13.3 or 4) between the long arm of chromosome 19 (19q13.3 or 4), and one had a balanced translocation between chromosome 15 and 19, t(15;19)(q15;q13.4).…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Seven previous case reports described the chromosomal translocations in MHL, each involving chromosome band 19q13.3 or 19q13.4. [8][9][10][11][12][13][14] Of the seven case reports, an immunohistological examination was performed in only two. We herein present the eighth case of MHL with a chromosomal translocation that also involved chromosome band 19q13.4, with an analysis of the immunohistological examination of the tumor and a review of the pertinent literature.…”
Section: Introductionmentioning
confidence: 99%